TINGKATAN PENGHIDUPAN BERKELANJUTAN PADA KELOMPOK NELAYAN WANA SEGARA KERTIH KELURAHAN KEDONGANAN, KECAMATAN KUTA, KABUPATEN BADUNG, BALI - Lestari, Putri; Setiawan, I Gede Bagus Dera (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
There are five livelihood assets that must be possessed, namely human capital, natural capital, social capital, financial capital, and physical capital. The purpose of this research is to measure and analyze the condition of sustainable livelihood assets and to determine the household income obtained by the fishermen group. The study was conducted in the Kedonganan Village on the Wana Segara Kertih Fishermen Group. The population and sample used were 61 people whose primary livelihood is as fishermen. The method used was quantitative descriptive. Assessment used an interval scale by interpreting the average score according to its rating category. The research results show that human capital is rated very high, while natural capital and physical capital received lower scores with a category of doubt. Social capital received a very high rating. The average income of fishermen outside the fisheries sector is Rp 14,549,043.72 per year, while in the fisheries sector it is Rp 51,869,672 per year, resulting in an average household income of fishermen of Rp 41,982,191 per year. Research recommendations emphasize the need to improve financial capital management and conservation of natural resources to maintain the sustainability of marine resources.